Effect Of Emotional Fatigue On Employee Behavior With Moderate Variables Of Work Stress (Case Study On Secretáriado Da Comissão Função Publica (SCFP) - Juvenal Baptista Mendonça; I Gede Riana; Dr. Augusto D. Soares (ABM: International Journal of Administration, Business and Management, 2022)
This study aims to analyze and explain (1) The effect of emotional fatigue on employee deviant behavior, (2) The effect of work stress on employee laying behavior, (3) The role of work stress in moderating the effect of emotional fatigue on employee behavior. The study was conducted at the Comissão da Função Pública (CFP) secretariat office. This study uses quantitative research methods, data collection using questionnaire instruments, and data analysis using Moderate Regression Analysis (MRA) using 110 respondents. The results of this study concluded that emotional fatigue had a positive effect on employee deviant behavior. However the work stress variable in this study has a positive influence in moderating the relationship of emotional fatigue to employee deviant behavior.